2009
DOI: 10.1111/j.1478-3231.2009.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic gene expression in response to hepatoprotective levels of zinc

Abstract: Background Zinc (Zn) administration at non-toxic doses protects against the hepatotoxicity produced by many agents, but the underlying mechanisms remain elusive. Aim To examine the basis of Zn-induced generalised hepato-protective effects. Methods Rats and mice were given Zn at known hepato-protective levels (100 μmol ZnCl2/kg/day, s.c., for 4 days) and molecular responses were assessed. Results Zn treatment produced changes in 5% of the genes on custom-designed mouse liver array and Rat Toxicology-II ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Zinc transporter ZIP14 functions in hepatic zinc, iron and glucose homeostasis during the innate immune response, but also mediates fibrosis progression through regulation of zinc-dependent endoproteinases highly expressed in hepatic stellate and Kupffer cells [32]. In vitro and in vivo studies addressing the role of zinc supplementation at non-toxic doses further demonstrated that zinc protects against hepatotoxicity, which is likely mediated by its regulatory role of acute-phase protein genes [2]. Thus, it is tempting to speculate that the altered innate immune response caused by zinc deficiency [5] might also be responsible for the altered disease progression of PSC patients observed in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Zinc transporter ZIP14 functions in hepatic zinc, iron and glucose homeostasis during the innate immune response, but also mediates fibrosis progression through regulation of zinc-dependent endoproteinases highly expressed in hepatic stellate and Kupffer cells [32]. In vitro and in vivo studies addressing the role of zinc supplementation at non-toxic doses further demonstrated that zinc protects against hepatotoxicity, which is likely mediated by its regulatory role of acute-phase protein genes [2]. Thus, it is tempting to speculate that the altered innate immune response caused by zinc deficiency [5] might also be responsible for the altered disease progression of PSC patients observed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In chronic liver dysfunction, particularly in cases of ALD and viral liver disease, serum zinc levels are reduced compared to healthy control populations [7,8]. A microarray analysis profiling genetic patterns associated with zinc supplementation indicated that zinc has a highly hepatoprotective function when administered at non-toxic doses [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that AP decreased Fmo5 mRNA expression, but CGA failed to increase it. MT is a family of cysteine-rich, low-molecular-weight proteins, and it has been reported to protect against oxidative stress injury induced by exogenous agents (Bauman et al, 1991;Liu et al, 2009). In addition, there is a report that MT-null mice were more susceptible than wild mice to AP-induced hepatotoxicity, whereas zinc pretreatment, a method of inducing MT expression, protected against AP-induced hepatotoxicity (Liu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the nuclei of P. lividus embryos, HSF binds HSE under physiological growth conditions (18-20°C), and this binding activity increases upon heat shock (31°C) (Sconzo et al 1997). Furthermore, metal treatment results in synthesis of HSPs and the induction of metallothionein (MT) genes (Forti et al 2010;Liu et al 2009;Natoli et al 2009). This induction is mediated by the cis-acting DNA element, the metal-responsive element (MRE).…”
Section: Introductionmentioning
confidence: 97%